Peningkatan Kualitas Konten sebagai Strategi Promosi Desa Wisata - Eny Endah Pujiastuti; Keny Rahmawati; Nurul Retno Hapsari; Satrio Tegar Gunung Korrag; Muhammad Irfan Mu’afi; Ahmad Zaki; Virginia Ayu Sagita; Arif Hervianto (Fakultas Ekonomi dan Bisnis Unversitas Islam Raden Rahmat, 2024)
Digital marketing has enormous potential for promoting and advertising tourism in general, but its impact becomes more apparent when we concentrate on the international target audience of rural tourism and the challenges and costs of reaching them with traditional marketing initiatives. One marketing strategy that can be used to attract customers on social media is to use a content marketing strategy (Krasniak et al., 2021). Digital content marketing strategies theoretically help increase tourist interest in visiting (Holliman and Rowley, 2014). The main problem formulation is how to improve the quality of promotion (digital marketing) so that it can encourage tourists to visit tourist villages, especially international tourists. The aim of the activity is to improve the ability of tourist village managers to make promotions (digital marketing) of higher quality. The approach used is a community-based approach with a business incubator model. The steps taken are training and mentoring. The activity location is in the Jenissari Tourism Village, Cangkringan, Umbulharjo, Sleman, DIY. The results of activities increase the ability to create content in the form of photos and videos. Making videos with publicists via Tripadvisor media so that information about the tourism village of Titiksari can reach the international market. Increasing the quality of content on the website can improve the quality of information and meet tourists' needs for information about the destination they are going to